2015
DOI: 10.3390/agriculture5020313
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Apple Pomace as a Feed Additive to Enhance Growth Performance of Growing Pigs and Its Effects on Emissions

Abstract: Apple pomace is a by-product from the apple processing industry and can be used for the production of many value-added compounds such as enzymes, proteins, and nutraceuticals, among others. An investigation was carried out to study the improvement in the protein content in apple pomace by solid-state fermentation using the fungus Phanerochaete chrysosporium by tray fermentation method. The effect of this protein in terms of how it enriched apple pomace as animal feed for pigs has also been studied. There was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Results in this research were completely agreed with the results of many studies reporting an increase in crude ash and protein content as a result of the fermentation of industrial by-products with various microorganisms including P. ostreatus and P. chrysosporium (Lateef et al, 2008;Ajila et al, 2015;Madrera et al, 2017;Yasar and Tosun, 2018b). In our study, the rate of increased crude ash and protein content by P. ostreatus and P. chrysosporium fermentation was comparably higher than these results in the above studies.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Results in this research were completely agreed with the results of many studies reporting an increase in crude ash and protein content as a result of the fermentation of industrial by-products with various microorganisms including P. ostreatus and P. chrysosporium (Lateef et al, 2008;Ajila et al, 2015;Madrera et al, 2017;Yasar and Tosun, 2018b). In our study, the rate of increased crude ash and protein content by P. ostreatus and P. chrysosporium fermentation was comparably higher than these results in the above studies.…”
Section: Resultssupporting
confidence: 91%
“…Fungal fermentations of agricultural waste products in solid state fermentation (SSF) resulted in remarkable nutritional and chemical benefits in respect to adding value to these products (Kurt and Buyukalaca, 2010). Several fungal microorganisms were successfully used in various conditions of SSF using apple pomace for the enrichment of nutrients (Villas-Boas et al, 2003;Albuquerque et al, 2006;Vendruscolo et al, 2008;Ajila et al, 2015;Madrera et al, 2017), for improvements of antioxidant enzyme activities (Zheng and Shetty, 2000;Joshi and Devender, 2006;Ajila et al, 2011) and aromatic compounds (Ricci et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In large-scale apple juice industry, about 70-75% of apples are utilised for juice and the remaining 25-30% is the by-product, apple pomace (AP), which is susceptible to biodegradation and is a problem for manufacturers (Grigoras et al, 2013). Wet apple pomace (AP) is most commonly used for animal feed or as fertiliser for soil agglomeration (Ajila et al, 2015). As AP is a material with high moisture and sugar content, its direct disposal in landfills can cause serious environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Apple pomace is a promising source of different functionally important bioactive compounds: carbohydrates, proteins, fatty acids, phenolic compounds, vitamins, minerals and others, with a wide range of food applications. Moreover, apple pomace can be widely used for obtaining several bioactive compounds (García et al, 2009;Kalinowska et al, 2014;Rabetafika et al 2014;Ajila et al, 2015;Perussello et al 2017;Waldbauer et al, 2017). Preclinical studies have found that apple pomace and its isolated extracts improved lipid metabolism, antioxidant status and gastrointestinal function, and had a positive effect on metabolic disorders (e.g., hyperglycemia, insulin resistance, etc.)…”
Section: Introductionmentioning
confidence: 99%